Description of radiological findings in psitacids seized and kept in a rescue center in Tingo María, Huánuco – Peru - Grandez R., Ricardo (2021)
Illegal trafficking in birds, especially parrots, is frequent in Peru. The methods of capture and the poor conditions of transport and captivity cause them to suffer trauma and physical injuries, which can damage bone structures. These animals are confiscated and sent to rescue centres to rehabilitate them for their reintroduction. In the present study, the radiographic records of nine parrots from a rescue centre in Tingo María, Peru (Ara chloropterus, Amazona farinosa, Ara macao and Pionus menstruus [one per species], two Ara militatis, and three Ara ararauna) were evaluated. Most of the injuries occurred in the forelimb (77%), especially in the distal portion (44%); the radius and ulna being the most affected. The most common complications were exuberant bony callus, poor consolidation and osteomyelitis; and the clinical sequelae were loss of flight capacity and marked claudication. The lesions found prevent the reintroduction of these birds to their natural habitat.